If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + -4) = -60 Reorder the terms: 3(-4 + 4x) = -60 (-4 * 3 + 4x * 3) = -60 (-12 + 12x) = -60 Solving -12 + 12x = -60 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 12x = -60 + 12 Combine like terms: -12 + 12 = 0 0 + 12x = -60 + 12 12x = -60 + 12 Combine like terms: -60 + 12 = -48 12x = -48 Divide each side by '12'. x = -4 Simplifying x = -4
| (-3)+3=18 | | .9x+2.3=-6.4 | | 3/5=(a-7.46)/a | | (-3)+3=8 | | 2u+5=9 | | 3/5=a/(a+7.46) | | 11x-1=9x+21 | | 3(4x+7)=-51 | | 14-4x+24=130-5x-15 | | 4n+2=10 | | 6+2h=10 | | 3/5=a/(a+7.5) | | -1.5+0.15x=0 | | 9a^2=-a^2-18 | | -6(-2+4x)=-252 | | a^2=-a^2-18 | | t/29.4=5.5/4.2 | | x^2=-a^2-18 | | A/8.4=21.3 | | 6(4-x)=30 | | H/19.1+1.5=13.5 | | S/7.3=5.6 | | 3(1x-1)=30 | | 2x+(-45)=728 | | -2(3x-9)=12 | | 35w=56 | | 3(x+3)4-2x+12=0.5 | | 7(2+2x)=-56 | | (5x+4/4x+3)/(x-10/x-8) | | 24-a/3=-12 | | 4g+7-2g=5g-5 | | 11x-7x=12 |